TLR4 Promotes and DAP12 Limits Obesity‐Induced Osteoarthritis in Aged Female Mice. (4th October 2018) - Kalaitzoglou, Evangelia; Lopes, Erika Barboza Prado; Fu, Yao; Herron, Jacquelyn C; Flaming, Josiah M; Donovan, Elise L; Hu, Yanqing; Filiberti, Adrian; Griffin, Timothy M; Humphrey, Mary Beth
ABSTRACT: Aging and female sex are the strongest risk factors for nontraumatic osteoarthritis (OA); whereas obesity is a modifiable risk factor accelerating OA. Prior studies indicate that the innate immune receptor toll‐like receptor 4 (TLR4) mediates obesity‐induced metabolic inflammation and cartilage catabolism via recognition of damage‐associated molecular patterns and is increased with aging in OA joints. TLR4 responses are limited by innate immunoreceptor adapter protein DNAX‐activating protein of 12kDA (DAP12). We undertook this study to test the hypothesis that TLR4 promotes, whereas DAP12 limits, obesity‐accelerated OA in aged female mice. We fed 13‐ to 15‐month‐old female WT, TLR4 KO, and DAP12 KO mice a high‐fat diet (HFD) or a control diet for 12 weeks, and changes in body composition, glucose tolerance, serum cytokines, and insulin levels were compared. Knee OA was evaluated by histopathology and μCT. Infrapatellar fat pads (IFPs) were analyzed by histomorphometry and F4/80+ crown‐like structures were quantified. IFPs and synovium gene expression were analyzed using a targeted insulin resistance and inflammation array. All HFD‐treated mice became obese, but only WT and TLR4 KO mice developed glucose intolerance. HFD induced cartilage catabolism in WT and DAP12 KO female mice, but not in TLR4 KO mice. Gene‐expression analysis of IFPs and synovium showed significant differences in insulin signaling, adipokines, and inflammation between genotypes and diets. Unlike young mice, systemic inflammation was not induced by HFD in the older female mice independent of genotype. Our findings support the conclusion that TLR4 promotes and DAP12 limits HFD‐induced cartilage catabolism in middle‐aged female mice. © 2018 The Authors JBMR Plus published by Wiley Periodicals, Inc. on behalf of American Society for Bone and Mineral Research.